2014
DOI: 10.1177/030089161410000214
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Combined PET/CT to Assess Regional Lymph Node Involvement in Gastric Cancer

Abstract: The accuracy of PET/CT is low and it is not a useful tool in the staging of gastric cancer overall in early gastric cancer and in signet-ring-cell carcinoma. Furthermore, the sensitivity of PET/CT could be inferior to that of CECT in the diagnosis of regional lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 21 publications
(32 reference statements)
1
29
0
Order By: Relevance
“…In this study, the authors reported that PET-CT was superior for detecting primary tumors compared to CT (67 vs. 55 %, p = 0.04). In this study, the proportion of patients with signet ring cell carcinoma was similar to that in our study [16]. In general, signet ring cell carcinoma is less sensitive to PET-CT.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, the authors reported that PET-CT was superior for detecting primary tumors compared to CT (67 vs. 55 %, p = 0.04). In this study, the proportion of patients with signet ring cell carcinoma was similar to that in our study [16]. In general, signet ring cell carcinoma is less sensitive to PET-CT.…”
Section: Discussionsupporting
confidence: 88%
“…1c, d). Park et al found both of these imaging methods to be inadequate for detecting regional lymph nodes, when compared with postoperative pathologic results [16]. In another study, there was similar imaging accuracy on PET- CT and CT for detecting lymph node metastases (71.8 and 69.2 %, respectively) [15].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it is difficult to diagnose metastasis when the metastatic tumor size is small [2]. It has been reported that CECT sensitivity, specificity, and accuracy for lymph node metastasis (LNM) detection were 25-51%, 79-92%, and 64-72%, respectively [3, 4]. It is sometimes difficult to judge whether a tumor has invaded into an adjacent organ and is unresectable.…”
Section: Introductionmentioning
confidence: 99%
“…However, FDG-PET/CT did not show additional diagnostic power for LNM compared to CECT where sensitivity, specificity, and accuracy of FDG-PET/CT vs. CECT were 34-41% vs. 51-75%, 88-100% vs. 51-92%, and 51-58% vs. 64-72%, respectively [3, 4]. FDG-PET/CT also showed low sensitivity for peritoneal metastasis [7] and a high detectability of liver and lung metastasis [8], as did CECT.…”
Section: Introductionmentioning
confidence: 99%